THE EFFECT OF CORPORATE GOVERNANCE ON FINANCIAL DISTRESS - Fitri Humairoh; Suci Nurulita (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
This research aims at examining the effect of the board of directors, audit committee, managerial ownership, and institutional ownership on financial distress in manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The population in this research are manufacturing companies listed on the Indonesia iStock iExchange for the i2015-2020 period. The sampling technique in this research used a purposive sampling technique and obtained a sample of i13 companies with a total of 78 data observations. The data analysis method used is multiple regression analysis. The results of this research indicated that institutional ownership affected financial distress, while the board of directors, audit committee, managerial ownership, and independent commissioner did not affect financial distress.